2010
DOI: 10.1097/lgt.0b013e3181dc1e45
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the Vulvar Clinic

Abstract: Most women attending the vulvar clinic have a reduced quality of life. Attending a dedicated multidisciplinary clinic is associated with an improvement in quality of life, but anxiety and depression scores are unchanged. This study is limited by small numbers, and further larger studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Also, in this pilot study, according to HAM-A and HAM-D scores, 52% and 26% of patients with vulvar conditions had scores of eight and higher. Anxiety scores were the highest for vulvodynia, whereas the depression scores were the highest in erosive lichen planus and eczema 22. In our study, HAM-A scores were significantly higher in the VD group than in the control group.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Also, in this pilot study, according to HAM-A and HAM-D scores, 52% and 26% of patients with vulvar conditions had scores of eight and higher. Anxiety scores were the highest for vulvodynia, whereas the depression scores were the highest in erosive lichen planus and eczema 22. In our study, HAM-A scores were significantly higher in the VD group than in the control group.…”
Section: Discussioncontrasting
confidence: 47%
“…Hickey and Bell22 showed that 23 patients who underwent the Dermatology life Quality Index questionnaire in vulvar clinic were affected slightly, moderately, or severely. Also, in this pilot study, according to HAM-A and HAM-D scores, 52% and 26% of patients with vulvar conditions had scores of eight and higher.…”
Section: Discussionmentioning
confidence: 99%
“…It is proven that visiting a dedicated, multidisciplinary clinic is associated with an improvement in QoL (38). Therefore, a multidisciplinary, well-trained health care team of a dermatologist collaborating with a gynaecologist, urologist, (dermato-) psychologist or sexologist would be of excellent value for the comprehensive management of genital psoriasis and its implications.…”
Section: Discussionmentioning
confidence: 99%
“…They are also important in developing service provision, particularly for smaller subspecialty areas such as vulval dermatology. Furthermore, it has been shown by previous qualitative studies that vulval diseases cause a reduction in QoL 10,11 . It is therefore important that we use patient and clinician assessment tools when monitoring this condition.…”
Section: Discussionmentioning
confidence: 99%